Atención de enfermería en pacientes geriátricos con cáncer en la unidad de cuidados críticos - Cando Maldonado, Jhajaira Alexandra (2025)
Introduction: The study analysed nursing care in geriatric cancer patients in the Critical Care Unit. The aging population and the increase in cancer cases in Ecuador have shown the need for specialized care. The main objective was to determine the current nursing care and the protocols used. Methods: A survey was applied to 15 nurses, most of whom showed moderate knowledge of palliative care and recognized the importance of psychological support and continuous monitoring of medication.93.3% of respondents said that psychological support is essential, and 73.3% said that they always apply hygiene protocols. However, 40% of professionals do not participate in training on the care of these patients, which reflects a need for continuous training. The difficulty in managing nutritional needs and communication with the medical team were identified as areas for improvement.It was concluded that, although the care provided generally complies with the standards, it is essential to implement a specific protocol for geriatric patients with cancer and promote constant training for staff. This would guarantee comprehensive care that improves the quality of life of patients in the terminal stage.